How E-Portfolio Facilitates Deep Learning in the Speaking Course of Second-Semester EFL Students - Ni Luh Komang Tria Prismayanti; Shabnam Heydarzade; I Wayan Heka Arcana Putra (Universitas Pendidikan Ganesha, 2026)
Speaking is one of the most crucial skills in English language learning as it enables learners to communicate ideas effectively. However, many EFL students still experience difficulties in developing their speaking performance due to limited engagement and surface-level learning during the learning process. Previous studies have primarily examined the use of e-portfolios as assessment tools or reflective platforms, with limited attention to their role in facilitating deep learning in speaking courses. Moreover, how e-portfolios support the integration of mindful, meaningful, and joyful learning under the concept of deep learning in improving students’ speaking performance remains underexplored. Therefore, this study investigates how e-portfolios facilitate deep learning in the speaking course of second-semester EFL students by integrating mindful, meaningful, and joyful learning. Using a qualitative phenomenological design, data were collected from ten students through document analysis, such as videos, peer feedback, reflections, and semi-structured interviews, and were thematically analyzed. The findings revealed that e-portfolios promoted mindful learning through reflection and awareness of progress, meaningful learning through connections between tasks and students’ real-life experiences, and joyful learning through motivation, confidence, and satisfaction. Although students faced challenges such as limited time and emotional discomfort in giving or receiving feedback, the overall results showed that e-portfolios effectively fostered a deeper, more reflective, and enjoyable learning experience in speaking courses.